Composite Anion Exchange Membranes from Quaternized Poly(arylene ether ketone) and Quaternized Titanate Nanotubes with Enhanced Ion Conductivity. Issue 6 (3rd December 2019) - Lu, Y.; Hu, Z.; Liu, Y.; Buregeya, I.; Pan, X.; Li, N.; Chen, S.
Abstract: The present work deals with the fabrications and characterizations of nanocomposite anion exchange membranes composed of quaternized titanate nanotubes (QTNT) and quaternized poly(arylene ether ketone)s (QPAEK) for fuel cell applications. QTNT was synthesized by coupling reaction of (3‐chloropropyl) trimethoxy silane on titania nanotubes (TNT) and Menshutkin reaction with trimethylamine. The nanocomposite membranes were prepared by the facile solvent casting method. The introduction of the quaternary ammonium groups generates strong interfacial interactions and contributes to the better compatibility between the QPAEK and QTNT. A rather small amount of QTNT (no more than 1 wt.%) incorporated into the membrane substantially enhanced the performance of the obtained QPAEK/QTNT nanocomposite membranes, including the better solvent resistance, dimensional stability, ion conductivity, chemical stability and fuel cell performance. The QPAEK/QTNT‐1 membrane exhibited an appreciable ion conductivity of 52.5 mS cm −1, swelling ratio of 10% at 80 °C. It also produced the maximum power density of 62.8 mW cm −2, which was 1.4 times as high as that for the control QPAEK membrane (46.1 mW cm −2 ) in a H2 /O2 fuel cell at 80 °C and 100% relative humidity (RH). It gives good prospect for the QTNT as inorganic nanofillers in polymer electrolyte membrane fuel cell applications.